Does consultation improve decision-making? - Isopi, Alessia; Nosenzo, Daniele; Starmer, Chris (Springer, 2014)
This paper reports an experiment designed to test whether prior consultation within a group affects subsequent individual decision-making in tasks where demonstrability of correct solutions is low. In our experiment, subjects considered two paintings created by two different artists and were asked to guess which artist made each painting. We observed answers given by individuals under two treatments: In one, subjects were allowed the opportunity to consult with other participants before making their private decisions; in the other, there was no such opportunity. Our primary findings are that subjects in the first treatment evaluate the opportunity to consult positively, but they perform significantly worse and earn significantly less.